Two decades of plans: what effects on the growth of the handicraft sector in Algeria - Benlamoudi, Djalila; Derbal, Soumeia; Boussouak, Amel; Djedidi, Raouda; Djedidi, Samiha (The International tax journal, 2025)
This research paper addresses the most important reforms implemented in the handicrafts sector in Algeria. We focus on the developments that the sector has undergone in this regard within the framework of the two development strategies, Horizons 2010 and 2020, which outline the key measures supporting sector growth and enhancing its capabilities in the face of globalization and trade liberalization challenges. After discussing the concept and characteristics of the sector in Algeria, we present the main achievements that the sector has attained under the described reforms.